2015
DOI: 10.1039/c5ra00746a
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of g-BC3and t-BC3phases

Abstract: The calculated electronic band structure show that thephase is a narrow band gap semiconductor constructed from ,...., ABAB stacking sequence. Whereas 3 BC t − phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…It also changes the gap from indirect to direct. It has been found that mBJ succeeds in bringing the calculated energy gap of I close to the experimental value (3.65 eV), 7 as is expected from this approach, [17][18][19] see Fig. S2 (ESI †).…”
Section: Salient Features Of the Electronic Band Structuresupporting
confidence: 72%
See 1 more Smart Citation
“…It also changes the gap from indirect to direct. It has been found that mBJ succeeds in bringing the calculated energy gap of I close to the experimental value (3.65 eV), 7 as is expected from this approach, [17][18][19] see Fig. S2 (ESI †).…”
Section: Salient Features Of the Electronic Band Structuresupporting
confidence: 72%
“…Therefore, the accuracy of the results will be very sensitive to the selection of the exchange-correlation potential (XC), which plays an important role in the determination of the energy gap. Based on our experience in using different XC potentials (LDA, PBE-GGA, EV-GGA, LDA-mBJ and PBE-GGA-mBJ) on several systems whose energy band gaps are known experimentally, [17][18][19] we nd that PBE-GGA-mBJ gives the best agreement with the experimental data. [17][18][19] This motivated us to use PBE-GGA-mBJ to calculate the band structure and hence the rst-order linear optical dielectric functions of I and II.…”
Section: Complex Rst-order Linear Optical Dispersionmentioning
confidence: 95%
“…Therefore, we can compare our calculated electronic band structure with previous calculations using different methods and different exchange-correlation potentials [20][21][22][23], in general reasonable agreement was found in the matter of bands dispersion. Based on our previous experiences with mBJ on similar systems [40,41] therefore, using mBJ to calculate the electronic band structure of LaFe 4 X 12 (X = P, As and Sb) compounds should show better band splitting than that obtained from LDA and GGA and hence more accurate optical properties due to better optical transitions between the bands. Future experimental work will testify our calculated results.…”
Section: Electronic Band Structure and Density Of Statesmentioning
confidence: 98%
“…It is a local approximation to an atomic "exact-exchange" potential and a screening term. In the recent years due to the improvement of the computational technologies, it has been proven that the first-principles calculation is a strong and useful tool to predict the crystal structure and its properties related to the electron configuration of a material before its synthesis [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%